THE SUBSTANTIATION OF LOCAL TREATMENT OF PURULENT WOUNDS BY PHARMACOCYTES WITH DIOXYDIN - S. Fedzianin (Сеченовский вестник)
The article discusses the topical purulent wounds treatment with pharmacocytes and dioxidin. MIC, MIC50 and MIC90 of dioxidin were tested on 77 strains, isolated from the purulent wounds of various localizations. The study of the degree of dioxidin inclusion in erythrocyte pharmacocytes involved 25 blood samples of volunteer patients. The study of the concentration of dioxidin and dioxidin, included in erythrocyte pharmacocytes, in purulent wounds in the 1 phase of wound process was performed in 35 volunteer patients.Standard bacteriological methods were used in the work. Dioxydin included in the ghosts by hypotonic hemolysis. The concentration of dioxydin in the erythrocyte ghosts determined by high performance liquid chromatography on Agilent 1260 liquid chromatograph. For the destruction of erythrocyte ghosts thereto distilled water was added and treated for 10 minutes in an ultrasonic bath of «Sapphire». Microscopic examination of erythrocyte ghosts was performed by light microscopy immersion in the native smear on the automated complex Leica.MIC90 of all strains of the leading pathogens of infections in surgery was 106,25 μg/ml. It was found that the erythrocyte ghosts are containers for dioxydin. The average concentration of dioxydin in them is 2151.72 ± 17.53 μg/ml, which is 6,9 times higher than the MIC90 to the majority of representatives of the microﬂora of purulent wounds. The pharmacocytes with dioxydin create a prolonged bactericidal concentration of dioxydin in purulent wounds.